ANALISIS PENGORGANISASIAN DALAM PENANGGULANGAN BENCANA MELALUI KELURAHAN SIAGA BENCANA DI KELURAHAN JOMBLANG, KECAMATAN CANDISARI, KOTA SEMARANG - Rosa Pevitanada; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The territory of Indonesia is a ring of fire area and is in the meeting of three tectonic plates potentially against the threat of natural disasters. Semarang city is a city with high disaster risk class. Given that the community is the biggest victims and first in facing disaster, the government has developed a community-based disaster risk reduction program. Community-based disaster risk reducation efforts in Semarang implemented through the establishment of Kelurahan Siaga Bencana (KSB). Jomblang is one of the KSB in Semarang City with the highest incidence of disaster events in 2016. In KSB Jomblang needed active participation from the community. This study aims to describe the implementation of organizing in disaster management in KSB Jomblang as well as supporting and inhibiting factors in the implementation of organizing. This research uses qualitative method with descriptive analysis model. The results of this study indicate that in the implementation of organizing KSB Jomblang when viewed from the process of organizing; the details of work, division of labor, grouping work, coordination of work, monitoring and reorganization has not been implemented optimally. Supporting factors in organizing KSB Jomblang are the high of social and tolerance, a division of labor according to skill, disaster administration has been running, and support from various parties. While the inhibiting factors are the differences of perception about the objectives, limited resources, the unclear division of work, lack of coordination, and the apathy of Karang Taruna. Suggestions that can be given include KSB Jomblang need to restructure and reorganize within their internal.